2020
DOI: 10.1186/s12859-020-03674-4
|View full text |Cite
|
Sign up to set email alerts
|

Developing the novel bioinformatics algorithms to systematically investigate the connections among survival time, key genes and proteins for Glioblastoma multiforme

Abstract: Background Glioblastoma multiforme (GBM) is one of the most common malignant brain tumors and its average survival time is less than 1 year after diagnosis. Results Firstly, this study aims to develop the novel survival analysis algorithms to explore the key genes and proteins related to GBM. Then, we explore the significant correlation between AEBP1 upregulation and increased EGFR expression in primary glioma, and employ a glioma cell line LN229 to identify relevant proteins and molecular pathways through p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…It is found that AEBP1 can promote the occurrence and development of tumors [32][33][34]. We found that AEBP1 is upregulated in CRC, which is the same as the results of previous studies [34,35].…”
Section: Discussionsupporting
confidence: 90%
“…It is found that AEBP1 can promote the occurrence and development of tumors [32][33][34]. We found that AEBP1 is upregulated in CRC, which is the same as the results of previous studies [34,35].…”
Section: Discussionsupporting
confidence: 90%
“…where k represents the lag order and is the error term. We use the F-test [23,[31][32][33][34][35][36][37][38][39] to verify the null hypothesis (Eq. ( 6)).…”
Section: Stationarity Test For Time Series Data Of Anthrax Casesmentioning
confidence: 99%
“…Furthermore, the second analysis in Ramsden's [4] publication implemented a Cox regression model [13][14][15] for survival analysis to test for the relationship between cholesterol level reduction and risks of death. The recovered data was split into two groups depending on whether the participant's cholesterol level decreased at the end of the MCE.…”
Section: Introductionmentioning
confidence: 99%